Stigma in Elderly Females with Stress Urinary Incontinence: A Latent Profile Analysis - Haochong He; Xiue Huang; Bijun Yu; Ye Liu; Shuyuan Mai; Le Ouyang; Qiaoling Zhang; Xiaoying Yan (Clinical and Experimental Obstetrics & Gynecology)
Background: Stress urinary incontinence (SUI) is a commonly occurring urological disorder in females, particularly among the elderly population. Females with SUI often experience significant stigma associated with their condition. This study aimed to investigate the current status of stigma among elderly females with SUI and analyze its heterogeneous subtypes. Methods: The Stigma Scale for Chronic Illness (SSCI) was used to survey 245 participants in two tertiary hospitals in Guangdong from November 2021 to September 2022. Latent profile analysis was employed to create a classification model, and variance and correlation analyses were conducted to assess the influencing factors. Results: A total of 245 elderly females with SUI participated in the survey. They had an average stigma score of 83.70 ± 13.88, consisting of self-stigma (48.64 ± 8.04) and perceived stigma (35.06 ± 6.80) scores. Latent profile analysis identified three distinct and comparable subtypes: the low-self-low-perceived group (14.69%), the high-self-medium-perceived group (49.38%), and the high-self-high-perceived group (35.91%). These subtypes exhibited statistically significant differences in all dimensions and the overall stigma score (p < 0.05) and were found to be correlated with the patient’s level of education, marital status, drinking habits, number of chronic illnesses, presence of diabetes, and frequency of urinary leakage (p < 0.05). Conclusion: This study demonstrates that elderly females with SUI face elevated levels of stigma, and it reveals distinct classification characteristics among them. Additionally, it emphasizes the importance of providing specific support and attention to individuals with higher levels of education, increased fluid intake, marital status, severe urinary leakage, and diabetes.